The formation of 3-Monochloropropanediol esters and Glycidyl esters during heat-induced processing using an olive-based edible oil - Ji, Yingrui; Lan, Dongming; Wang, Weifei; Goh, Kok Ming; Tan, Chin Ping; Wang, Yonghua (Multidisciplinary Digital Publishing Institute, 2022)
With the prevalence of edible diacylglycerol (DAG) oil, which is beneficial to human, the generation of 3-monochloropropanediol esters (3-MCPDE) and glycidyl esters (GE) as well as the stability of physical properties during heat-induced processing still need to be explored. In this study, the experiment used olive-based edible oil with different contents of DAG (40, 60, and 80%) to make crackers and fry chicken. They were heated at 160 and 180 °C to determine the changes in 3-MCPDE and GE, the crackers’ hardness and gumminess, and the physical properties of the oil. During baking and frying, 3-MCPDE decreased, while the content of GE slightly increased with the prolonged heating duration. Finally, 3-MCPDE and GE were lower than 1.25 mg/kg and 1.00 mg/kg, respectively. The AV increased proportionally as duration increased and POV was below 0.30 g/100 g. In general, the changes in 3-MCPDE and GE were related to the heating temperature and duration, and not significantly (p > 0.05) related to the content of DAG.